Associations between adrenarcheal hormones, amygdala functional connectivity and anxiety symptoms in children. (November 2018) - Barendse, Marjolein E.A.; Simmons, Julian G.; Byrne, Michelle L.; Patton, George; Mundy, Lisa; Olsson, Craig A.; Seal, Marc L.; Allen, Nicholas B.; Whittle, Sarah
Highlights: Adrenarcheal hormone levels were related to amygdala connectivity to visual cortical areas, insula and anterior cingulate. Adrenarcheal hormone levels were indirectly related to anxiety symptoms, through amygdala connectivity. These indirect associations were dependent on sex. Abstract: Objective: The transition from childhood to adolescence is a vulnerable period for the development of anxiety symptoms. There is some evidence that hormonal changes occurring during adrenarche, an early pubertal phase, might play a role in this increased vulnerability. Little is known about underlying brain mechanisms. Given the role of the amygdala-based fear circuit in anxiety, the current study aimed to investigate whether children's adrenarcheal hormone levels were associated with functional connectivity of the amygdala while processing fearful facial expressions, and how this in turn related to anxiety symptoms. Method: Participants were 83 children ( M age 9.53 years) who completed two morning saliva collections to measure levels of dehydroepiandrosterone (DHEA), its sulphate (DHEAS), and testosterone. They also completed the Spence Children's Anxiety Scale (SCAS), and viewed fearful and calm facial expressions while undergoing a functional MRI scan. Psychophysiological interaction (PPI) analyses were performed to examine amygdala connectivity and significant clusters were fed into a bootstrapping mediation model. Results: In boys, mediation analyses showed an indirect positive effect of testosterone on anxiety symptoms, which was mediated by amygdala-secondary visual cortex connectivity as well as amygdala-anterior cingulate connectivity. In girls, DHEAS showed a negative indirect association with anxiety symptoms mediated by amygdala connectivity to the fusiform face area and insula. Conclusion: The results indicate unique roles for adrenarcheal hormones in anxiety and suggest that amygdala connectivity may represent an important neural mechanism in these associations. Importantly, results reveal prominent sex differences in the biological mechanisms associated with anxiety in children undergoing adrenarche.